The Influence of Financial Literacy on Financial Satisfaction With Financial Behavior as Moderating Variable (Case Study on MSMEs in Sleman Regency, Yogyakarta) - Panjaitan, Yohannes Estrada; Gusaptono, R. Hendri; Satoto, Shinta Heru (Journal of Business Innovation and Research, 2023)
This study aims to explain the effect of financial literacy on financial satisfaction with financial behavior as a moderating variable. This research was conducted on SMEs in Sleman Regency, Yogyakarta with a total of 100 SMEs with the sample criteria that MSMEs have been operating for at least 1 year and provide primary needs. This study uses three variables. Data were tested using simple regression and moderated regression analysis. The results of the study show that financial literacy has a positive effect on financial satisfaction. In addition, it was found that financial behavior moderates the effect of financial literacy on financial literacy in MSMEs in Sleman Regency, Yogyakarta. This study shows that the financial literacy of MSME actors will influence their financial behaviour decisions so that the impact will be seen on their financial satisfaction.